From Dictatorship to Democracy :coping with the legacies of authorianism and totalitarianism/ edited by John H. Herz - "Herz,John H. (ed.)" (London, 1982)
An entrepreneurially oriented professor locates, either by accident or by design, an issue, crisis, or 'problem' which is deemed marketable and generates a symposium to fit it. If the design can be sold to a sponsor, the entrepreneur invites contributors, arranges meetings, coordinates production, and in time edits and publishes the finished product.
Keywords: West German Democracy